2015
DOI: 10.1002/ccr3.228
|View full text |Cite
|
Sign up to set email alerts
|

Integrating EMDR into an evolutionary‐based therapy for depression: a case study

Abstract: Key Clinical MessageWe present an intervention in a case of major depression, where eye movement desensitization and reprocessing (EMDR) therapy was integrated into an evolutionary-based psychotherapy for depression. At the end of the treatment and at follow up assessment we observed a more accepting disposition and decreased depressive but not anxiety symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
1
7
0
2
Order By: Relevance
“…Seven of these studies showed that this method results in faster and more effective treatment of negative life experiences and feelings than cognitivebehavioral therapy [16] . The results of this study are consistent and confirmatory with the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of these studies showed that this method results in faster and more effective treatment of negative life experiences and feelings than cognitivebehavioral therapy [16] . The results of this study are consistent and confirmatory with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…But, when uncomfortable or traumatic experiences are not sufficiently processed, that thought remains as disturbing. These disturbing memories create abnormal continuous reactions and brain can process them with eye movement or other bilateral stimulations adaptively [16] . Compared to the CBT method, one of the advantages of this approach is that the number of sessions is less, and its effectiveness is durable.…”
Section: Discussionmentioning
confidence: 99%
“…Outro exemplo é o estudo de caso publicado por Krupnik (2015) sobre os resultados do uso da dessensibilização e reprocessamento do movimento ocular (EMDR) com uma terapia de base evolucionista para a depressão, denominada tratamento da depressão em declive (TDD). A TDD trabalha em três fases: exploração, aceitação e ativação comportamental.…”
Section: Afirma Que Osunclassified
“…Trabalhos psicoterapêuticos com deprimidos a partir de uma perspectiva evolucionista têm sido realizados (e.g., Giosan, 2020;Giosan et al, 2020;Krupnik, 2015) e escalas que testam as previsões das hipóteses evolucionistas têm sido desenvolvidas, a exemplo daquelas citadas ao longo desta revisão (e.g., Barbic, Durisko, & Andrews, 2014;Bartoskova et al, 2018;Keller & Nesse, 2006). No entanto, ainda não existem relatos no Brasil da validação dessas escalas e nem da implementação de trabalhos psicoterapêuticos nessa abordagem com a depressão.…”
Section: Considerações Finaisunclassified
“…A novel integrative treatment, TDD-EMDR, has recently been suggested for treatment of depressive disorders (Krupnik, 2015a, Krupnik, 2015b. Although there are no enough data yet from comparative randomized controlled trials (RCTs) to make a definitive conclusion about the effectiveness of EMDR therapy for depression (Wood & Ricketts, 2013), it has been shown effective for depression in case (Bae, Kim, & Park, 2008;Broad & Wheeler, 2006;Grey, 2011;Rosas Uribe et al, 2010) and controlled studies (Hase et al, 2015;Hofmann et al, 2014).…”
Section: Evolutionary-based Therapies For Depressionmentioning
confidence: 99%